2018
DOI: 10.1186/s40425-018-0347-5
|View full text |Cite
|
Sign up to set email alerts
|

CAR T cell therapy for breast cancer: harnessing the tumor milieu to drive T cell activation

Abstract: BackgroundThe adoptive transfer of T cells redirected to tumor via chimeric antigen receptors (CARs) has produced clinical benefits for the treatment of hematologic diseases. To extend this approach to breast cancer, we generated CAR T cells directed against mucin1 (MUC1), an aberrantly glycosylated neoantigen that is overexpressed by malignant cells and whose expression has been correlated with poor prognosis. Furthermore, to protect our tumor-targeted cells from the elevated levels of immune-inhibitory cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 58 publications
3
75
0
Order By: Relevance
“…ligands for costimulatory molecules (21), providing cytokine signaling (45)(46)(47)(48)(49), and the prevention of inhibitory signals (50,51).…”
Section: Mutation Of the Ymfm Motif In The Icos Signaling Domain To Ymentioning
confidence: 99%
“…ligands for costimulatory molecules (21), providing cytokine signaling (45)(46)(47)(48)(49), and the prevention of inhibitory signals (50,51).…”
Section: Mutation Of the Ymfm Motif In The Icos Signaling Domain To Ymentioning
confidence: 99%
“…17 Other ACT therapies, including the novel genetic redirection of T cells following the engineering with TCR or CAR receptors, are being explored to assess the potential activity and safety in TNBC patients. 18,19 Recently, indeed, a number of clinical trials are recruiting TNBC patients to assess the potential activity and safety of anti-mesothelin or anti-MUC1 18 CAR-T cell infusions. Despite the striking outcomes achieved with the infusion of CD19 CAR-T cells in hematological malignances, 3 the experience in solid tumors has not yet produced the same encouraging results, due to the difficulties of how to select the appropriate target, to address T cells to the tumor and/or metastases, and to reduce the risk of toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…The use of combinatorial antigen sensing circuits, i.e., synthetic Notch, where engagement of a tissue-specific antigen by a surface receptor induces transcription of a CAR recognising a tumour-associated antigen [42][43][44] Reduction of CAR T cell affinity [45] Designing CAR T cells targeting antigens that contain tumour-specific modifications/mutations (i.e., mutated variant III of epidermal growth factor receptor; EGFRvIII) [46][47][48] Overcoming immunosuppressive tumour microenvironment (TME) CAR T cell transduction with dominant-negative transforming growth factor β receptor II (dnTGF-βRII)-a decoy receptor for immunosuppressive TGFβ produced by tumour [49] Introducing switch receptors transforming inhibitory cytokine signals into a stimulus (i.e., fusing immunosuppressive IL-4 receptor exodomain to the immunostimulatory IL-7 receptor endodomain) [50,51] Introduction of hypoxia-inducible factor 1-alpha (HIF-1α), a transcription factor stabilised in response to hypoxia, to CAR T cells resulting in increased CAR expression specifically in hypoxic TME [52] Co-expression of catalase to protect CAR T cells, as well as bystander T cells, from reactive oxygen species (ROS) in TME [53] Inhibition of adenosine receptors with their antagonists or shRNA to prevent immunosuppressive effects exerted by tumour derived adenosine [54] The remaining issue of CAR T cell therapy is the loss of expression of targeted antigen by the tumour during the treatment [39,47]. It has been suggested that only patients with homogenous antigen expression on all cancer cells should be treated with this approach to avoid recurrence.…”
Section: Possible Solution Referencesmentioning
confidence: 99%